MUTU LAYANAN DARI BAGIAN LAYANAN AKADEMIK TERHADAP KEPUASAN DOSEN DI UNIVERSITAS XYZ - Hartono, Henny (Economic Faculty, Attahiriyah Islamic University, 2017)
In carrying out duties in giving lectures, the lecturers receive services from the university and the department in charge to serve the needs of the lecturers at XYZ University is Academic Service (AS). This research intends to measure the satisfaction of the lecturers regarding the services provided by Academic Service of XYZ University. Data analysis tool used in this research is the Multiple Regression Analysis.The test results show that the responsiveness and assurance factors have dominant influence on lecturers’ satisfaction at XYZ University.The conclusion from this research is that the five factors of service quality together have significant effect on lecturers’ satisfaction at XYZ University. Ketwords: lecturers satisfaction, academic service quality